The Effect of Sprint Start Speed on Lower-limb Stiffness in Sprint Runners - Mansour Eslami; Effat Hoseinzadeh; Alireza Safaei Kenari (Biyumikānīk-i varzishī)
Objective: Lower extremity stiffness is associated with variables such as the frequency and length of running steps, the amount of muscle force and power production. Previous studies showed contradictory findings regarding the relationship between lower extremities joints stiffness and start velocity. Sprint start can be highly affected by two key components of lower limb stiffness, namely, force and time. However, no research has yet investigated the effect of start velocity changes on lower–limb stiffness during sprint start. To test the effect of velocity changes on lower-limb stiffness during sprint start. Method: 15 male members of track and field were selected for this study. Leg stiffness was calculated dividing peak ground reaction force by the leg length. Joint stiffness was also estimated dividing the muscle moment of force by joint angular displacement. Subjects performed a start with three different speeds. Results: From low to high start velocity, means of leg stiffness, knee stiffness and ankle stiffness increased by 67.53%, 41.9% and 39.03% respectively. Conclusion: The findings show that lower-limb stiffness could be a key factor in changing runners' acceleration during sprint start.